Pemetaan Suhu dan Tekanan Udara terhadap Faktor Kepadatan Lalu Lintas di Ruas Jalan Wilayah Kabupaten Mojokerto - Agi Rahmantoko Erlangga; Hendrata Wibisana (Universitas Batanghari Jambi, 2026)
Mojokerto Regency, East Java, is a region with rapid population growth and high motor vehicle usage. This condition leads to significant traffic congestion, especially during peak hours, and contributes to increased exhaust gas emissions such as carbon dioxide (CO₂), carbon monoxide (CO), and sulfur dioxide (SO₂). These emissions not only deteriorate air quality but also affect temperature, air pressure, and public health. This study aims to: (1) calculate vehicle volume on major roads in Mojokerto Regency; (2) analyze the degree of saturation (DS) as an indicator of traffic density; (3) measure CO₂ emissions; and (4) map temperature and air pressure using Geographic Information Systems (GIS). The research method involved field surveys, direct observation, traffic volume data recording, and measurement of temperature, air pressure, and CO₂ concentration during peak hours in the morning (06.00–09.00) and afternoon (15.00–18.00). Data were analyzed using statistical approaches, regression, T-test, and ANOVA to identify relationships among variables. The results show that high vehicle volume is directly proportional to an increase in DS values, with several road segments approaching saturation. Furthermore, the increase in vehicle volume correlates with higher air temperature, air pressure, and CO₂ concentration. GIS-based mapping illustrates the spatial distribution of traffic density and environmental conditions. This study concludes that traffic management and sustainable transportation development are essential to reduce the negative impacts on the environment and public health in Mojokerto Regency.